EFFECT OF DIFFERENT PROBIOTICS ON SURVIVAL AND GROWTH RATE OF TILAPIA SEED (ORECHROMIS NILOTICUS) - Luh Deva Oktari; Ida Bagus Jelantik Swasta; Ni Nyoman Dian Martini (Berkala Perikanan Terubuk, 2022)
Tilapia is a potential fish for cultivation because it is able to adapt to environmental conditions with a wide salinity range. to increase the production of farmed fish, One way is to find better feed. The addition of probiotics in feed with fermented doses is expected to affect the process of food absorption in fish digestion and probiotics can intercept or kill pathogenic bacteria from the digestive system so that the feed is able to decompose complex compounds into simple ones. The purpose of this study is to find out how the effect of the use of different probiotics on fish feed on the growth of tilapia fry and to find out better probiotics between the two probiotics used. In this study, the population studied was all tilapia in the Ringdikit Fish Breeding Center. The samples that will be used in this study are 270 tilapia. Based on the results of data analysis with reference to the Quantitative Descriptive test  concluded that feeding fermentation with Probiotic A, Probiotic B and Control had an effect on increasing the weight of Tilapia and the survival rate of Tilapia. Treatment with Probiotic B had a higher weight gain compared to treatment with probiotic A and control.